Partner bereavement and risk of psoriasis and atopic eczema: cohort studies in the U.K. and Denmark. (11th January 2020) - Wong, A.Y.S.; Frøslev, T.; Forbes, H.J.; Kjærsgaard, A.; Mulick, A.; Mansfield, K.; Silverwood, R.J.; Sørensen, H.T.; Smeeth, L.; Schmidt, S.A.J.; Langan, S.M.
Summary: Background: Stress is commonly cited as a risk factor for psoriasis and atopic eczema, but such evidence is limited. Objectives: To investigate the association between partner bereavement (an extreme life stressor) and psoriasis or atopic eczema. Methods: We conducted cohort studies using data from the U.K. Clinical Practice Research Datalink (1997–2017) and Danish nationwide registries (1997–2016). The exposed cohort was partners who experienced partner bereavement. The comparison cohort was up to 10 nonbereaved partners, matched to each bereaved partner by age, sex, county of residence (Denmark) and general practice (U.K.). Outcomes were the first recorded diagnosis of psoriasis or atopic eczema. We estimated hazard ratios (HRs) and confidence intervals (CIs) using a stratified Cox proportional hazards model in both settings, which were then pooled in a meta‐analysis. Results: The pooled adjusted HR for the association between bereavement and psoriasis was 1·01 (95% CI 0·98–1·04) across the entire follow‐up. Similar results were found in other shorter follow‐up periods. Pooled adjusted HRs for the association between bereavement and atopic eczema were 0·97 (95% CI 0·84–1·12) across the entire follow‐up, 1·09 (95% CI 0·86–1·38) within 0–30 days, 1·18 (95% CI 1·04–1·35) within 0–90 days, 1·14 (95% CI 1·06–1·22) within 0–365 days and 1·07 (95% CI 1·02–1·12) within 0–1095 days. Conclusions: We found a modest increase in the risk of atopic eczema within 3 years following bereavement, which peaked in the first 3 months. Acute stress may play a role in triggering onset of new atopic eczema or relapse of atopic eczema previously in remission. We observed no evidence for increased long‐term risk of psoriasis and atopic eczema following bereavement. Linked Comment:  von Kobyletzki. Br J Dermatol 2020; 183:207 . Abstract : What's already known about this topic? Psychological stress is commonly cited as a risk factor for psoriasis and atopic eczema. However, clinical evidence supporting such associations is limited. Current epidemiological evidence for the relationship is limited by small sample sizes and difficulty measuring stress. What does this study add? In two population‐based cohort studies, there was no evidence of an increased risk of psoriasis associated with partner bereavement. There was a short‐term increased risk of atopic eczema in the 3 years following partner bereavement, which peaked during the first year. However, there was no evidence of an increased long‐term risk of atopic eczema. Acute stress may trigger onset or relapse of atopic eczema, leading to an increased risk of atopic eczema in the short term following partner bereavement. Linked Comment:  von Kobyletzki. Br J Dermatol 2020; 183:207 . Plain language summary available online